The Conversation on Extreme Weather - Horney, Jennifer A. (Baltimore, Maryland: Johns Hopkins University Press, 2025)
"This book explores how climate-driven events-like Texas storms, Hurricane Ian, and wildfire smoke-impact daily life. It brings awareness to inequalities and environmental risks and offers practical solutions for preparedness and managing eco-anxiety"
Keywords: Climatic changes -- Social aspects; Weather -- Environmental aspects; Environmental policy -- 21st century -- United States; Climatic extremes